Variance, heritability and correlations in wheat hybrid populations for grain yield and other agronomic characteristics - Camargo, Carlos Eduardo de Oliveira; Filho, Antonio Wilson Penteado Ferreira; Felicio, João Carlos (Pesquisa Agropecuaria Brasileira, 2000)
The objective of the present work was to estimate the variance, heterosis and heterobeltiosis, and the narrow-sense heritability values for grain yield , spike length, rachis internode length and height of wheat plants (Triticum aestivum L.), as well as the environmental, phenotypic and genetic correlations between these characteristics. Degrees of dominance were also estimated for all characteristics except for grain yield. The experiment was carried out at the Experimental Center, in Campinas, São Paulo State, Brazil, under a screen house condition on crosses of the standard height cultivar IAC-227 (P1) with four mexican lines: CMH 78.390/ CMH 77 A.917// CMH 79.215 (P2), CMH 79.959/2* CNO 79 (P3), CMH 79.481/CMH 77A.917 (P4) and CMH 80A. 747 (P5). The narrow sense heritability values for plant height (0.608-0.861), spike length (0.406-0.667), rachis internode length (0.545-0.781) and grain yield (0.421-0.550) indicated that the great part of the verified genetic variability in the hybrid populations for these traits were due to additive gene action. The phenotypic correlations between plant height with grain yield and between spike length and rachis internode length were positive and significant to all crosses, showing to have associations between these characters; however the obtained results suggest that large F2 populations will be required to ensure the frequency of desired recombinants, showing semidwarf plants with high yield potential.